Polymeric blends containing different carboxylic acids (2024)
A single-screw extruder was used to produce polymeric blends comprising recycled high-density polyethylene (HDPE) and thermoplastic starch (TPS). Carboxylic acids with varying lengths of carbon chains were used as compatibilizing agents in the blends. While the mechanical properties did not show significant differences among the blends containing com patibilizing agents, all exhibited superior results compared to those without a compatibilizing agent. Therefore, opting for the more cost-effective acid is advisable